Study of the rice yield variations under water saving scenarios using DSSAT crop model - Chih-Yu Hsieh; Hungyen Chen; Yi-Chien Wu; Chih-Yung Teng; Cheng-Hong Li (PLoS ONE, 2025)
The current instability of water resources poses a major challenge and may lead to a food shortage crisis. To address this issue and to cope with the challenges of future extreme weather events and insufficient water resources, it is imperative to develop water-saving cultivation measures. This study used the long-term historical yield data of three rice varieties, TK9, TNG67 and TCS10, from an agricultural research station in Taiwan, simulated two water-saving cultivation experiments using the DSSAT crop model, and established a yield model based on the water-saving ratio, aiming to recommend appropriate irrigation water for Taiwan rice varieties. The goal was to save water while ensuring that the yield is not affected. Through water-saving cultivation simulation experiments, we estimated that under the condition of maintaining more than 90% of rice yield, water-saving irrigation treatment of rice in two different cropping seasons can save about 48% to 100% and 42% to 61% of irrigation water respectively. For irrigation treatment during sensitive growth stages, significant water-saving effects can be achieved, which are about 40% to 75% and 55% to 91% respectively. This study suggests that in the case of water shortage, it is possible to consider moderately increasing the water-saving ratio and implementing irrigation during sensitive growth periods, so as to effectively cope with future water shortage scenarios and achieve sustainable rice production while saving water resources.